Pengembangan Perangkat Lunak Dokumentasi Persuratan Menggunakan Codeigniter Dengan Semantic Web Pada Unit Kerja Inspektorat Jenderal Kemnaker - Muhamad Romdoni Rachman Wijaya; Heru Nurwarsito; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Information technology began to be used to build an E-Government based government by applying information technology in its work system to facilitate the work process and service to the community. With the development of information technology in the Government is expected the State Civil Apparatus performance will be faster and efficient. In the work unit of Inspectorate General of the Ministry of Labor, incoming mail that has not been documented electronically and activities of disposition of incoming mail which has been by using manual book led to the process of searching document letters constrained when the archive of incoming mail so much and excessive use of paper very wasted state budget from various ministries/ government agencies. To facilitate the process of searching and tracking the incoming mail flow until the mail is completed, it is necessary to develop mail documentation application at Inspectorate General Ministry of Labor. In this case, the mail documentation application is built using the CodeIgniter framework with the application of semantic web in hopes to simplify the process of searching document letters.